Ecological perspective of disease‐resistance prevalence in Penaeus monodon. Issue 6 (15th July 2020) - Mondal, Debabrata; Mandal, Nripendranath
Abstract: The virulent nature of many suddenly evolved highly contagious pathogens is controlled by surroundings' environment and also by the population density in a particular biogeographical region. Worldwide, the white spot disease (WSD) caused by the contagious white spot syndrome virus (WSSV) has devastated the aquaculture of penaeid shrimp species. WSSV is a highly infectious waterborne pathogen. The black tiger shrimp or Penaeus monodon had developed resistance potential against WSD with no antibody‐mediated immunity. Many environmental factors including oceanic water current often play a major role in the nourishment as well as species richness of indigenous marine species. Here, we reported that oceanic water current might influence the disease‐resistance prevalence in P. monodon .